Republic of Iraq : Oil Revenue Management for Economic Diversification - World Bank (World Bank, Washington, DC, 2022)
This report - the first phase of a programmatic Iraq country economic memorandum (CEM) is structured around the themes of revenue management and economic diversification. These themes accord with the economic challenges faced by Iraq in the medium term but contrast with the short-termism of current Iraqi decision making, which is pushing for a rapid ramp-up of oil production - reducing diversification to finance a large up-front spending program which is detached from a vision of how to diversify the economy. Iraq's oil revenue boom will not be able to meet the expectations placed upon it without a range of supporting policies. Iraq should aim towards adapting its economy to strong weight of oil, as opposed to complete insulation of the non-oil economy from it or dependence on it. To address the myriad links between Iraq's economic challenges, the report takes a sequential approach to the analysis. Chapter one presents an overview of the fiscal aspects of prospective developments in the energy sector, and an outline of major obstacles to growth in the non-oil economy. Chapter two, a relatively high-level and abstract economic model is developed to study the impact of various options for spending the oil revenue windfall on the non-oil economy. Chapter three, the opportunities for the development of the non-oil economy are set out in more detail along with recommended next steps in the World Bank support to the government of Iraq.